2007
DOI: 10.1128/iai.01336-06
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Cytotoxic Activities of Subtilase Cytotoxin Produced by Shiga-Toxigenic Escherichia coli

Abstract: Subtilase cytotoxin (SubAB) is a recently identified AB5 subunit toxin produced by Shiga-toxigenic Escherichia coli. The A subunit is thought to be a subtilase-like, serine protease, whereas the B subunit binds to the toxin receptor on the cell surface. We cloned the genes from a clinical isolate; the toxin was produced as His-tagged proteins. SubAB induced vacuolation at concentrations greater than 1 g/ml after 8 h, in addition to the reported cytotoxicity induced at a ng/ml level after 48 h. Vacuolation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 38 publications
2
70
2
2
Order By: Relevance
“…Interestingly, such dramatic changes in the cytoplasm were not associated with induction of cytoplasmic chaperones. In contrast to Morinaga et al who associated the vacuolating activity with the B subunit of SubAB (Morinaga et al, 2007), we have observed only minimal changes after treatment with the mutant toxin, which can be explained by trace residual catalytic activity of SubA A272 B (Wolfson et al, 2008). Therefore, we must conclude that formation of the perinuclear vacuoles is downstream of BiP degradation and not an independent activity.…”
Section: Discusssioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Interestingly, such dramatic changes in the cytoplasm were not associated with induction of cytoplasmic chaperones. In contrast to Morinaga et al who associated the vacuolating activity with the B subunit of SubAB (Morinaga et al, 2007), we have observed only minimal changes after treatment with the mutant toxin, which can be explained by trace residual catalytic activity of SubA A272 B (Wolfson et al, 2008). Therefore, we must conclude that formation of the perinuclear vacuoles is downstream of BiP degradation and not an independent activity.…”
Section: Discusssioncontrasting
confidence: 99%
“…In accordance with other reports of the effects of SubAB on mammalian cells we observed vacuolization of HeLa cells after treatment with SubAB (Morinaga et al, 2007). Formation of intracellular vacuoles is a common response to some,but not all, stimuli causing ER stress in HeLa cells, such as RNAi of p97/VCP or extended inhibition of ERAD by proteasome inhibitors (Wojcik et al, 1996).…”
Section: Discusssionsupporting
confidence: 92%
See 3 more Smart Citations